Acute pancreatitis with an emphasis on infection - Schneider, Lutz; Büchler, Markus W.; Werner, Jens (Infectious disease clinics of North America, 2010)
This article reviews pathophysiologic theories as well as the diagnostics and management of severe necrotizing pancreatitis. This review emphasizes the effect of infectious agents initiating AP and the concepts for treatment of infected pancreatic necrosis.
Gesehen am 21.06.2023